ANALISIS KETERAMPILAN MAHASISWA CALON GURU DALAM MENJELASKAN KONSEP MENGGUNAKAN ANALOGI PADA PEMBELAJARAN FISIKA - Muchsin, Muchsin; Khumaedi, Khumaedi (Physics Communication, 2017)
In teaching and learning process, teachers found the difficulty to transfer of understanding the material about the current electricity and difference potential to the learners. The understanding of this material classified into difficult materials because its characteristic was abstract. This research was a qualitative reasearch that aims to show the student of physics education competence in explaining the physics concept used analogy in learning of physics. The subject of this reserach was the student of physics education of sixth semester students of Physics Education Program who are taking the course of Physics School II. The techniques of data collection used in the form of written-test, interview, and documentation. The result of the reserach showed that the student of Physics Education Program students in explaning the physics concept using analogy belonged to average category. They used their experience in explaining the abstract physics concept in dinamic electricity material that used analogy, could describe the potential of misconceptions toward the understanding of concept that would be accepted by the learners and could explain the difference of analogy used based on the characteristic of analogy which is not appropriate with the concept. The analogy reasoning pattern that used by the student of physics education in explaining physics concept used analogy was more dominant than that of inductive reasoning pattern. The dificulty factors of student of physics education in explaining the physics concept used analogy were existing at; 1) seeking of the right analogy, 2) connecting the analogy with the concept of dinamic electricity, 3) explaining the appropriate analogy with the concept. The student of physics education difficulties factors may be caused by their less conceptual understanding about physics concept in dinamic electricity. The solution to overcome this problem is candidat teacher needs to improve their understanding about concept of dynamic electricity to simplify acquiring the appropriate analogy and connect the concept of physics material which taught by using the anlogy.